An Investigation of EFL Students’ Attitudes Toward Culturally Responsive Pedagogy in Speaking Classes - Reskyani; Syarifuddin Dollah; Muhammad Basri (Universitas Sulawesi Barat, 2025)
Particularly in multicultural classrooms like those in Indonesia, culturally responsive teaching (CRT) provides inclusive practices that serve a variety of learners. With an emphasis on positive and negative answers across four aspects: experience, attitude, feeling, and belief, this research investigates students' perceptions of culturally responsive teaching implementation in an English-speaking class at Universitas Muslim Indonesia’s English Education Department. A qualitative case study design was used to gather information from 12 students using field notes, observations, interviews, and documentation. Miles and Huberman's interactive model was used in the analysis. According to the findings, most students thought culturally responsive teaching improved their motivation, cultural sensitivity, and involvement in class. Due to emotional discomfort or a lack of knowledge of artistic content, some students did, however, express fear and limited engagement. The research emphasizes how culturally responsive teaching may be both powerful and challenging for some people and contributes to improving it for consistent, emotionally inclusive teaching methods. In theory, this research advances culturally responsive teaching in higher education; in practice, it gives lecturers guidance on how to create speaking exercises that are inclusive of all cultures while addressing their students' anxiety and engagement issues. The findings suggest that higher education institutions should integrate Culturally responsive teaching (CRT) as a core component of teacher training and curriculum development, particularly in English language education. Lecturers need continuous professional development to effectively design and facilitate culturally inclusive speaking activities that reflect students’ diverse backgrounds, mitigate anxiety, and foster meaningful engagement. Institutional policies must support culturally responsive pedagogy by encouraging reflective teaching practices, developing culturally rich teaching materials, and creating safe classroom environments where emotional discomfort can be addressed constructively. Future studies are recommended to examine CRT in larger and more diverse populations and to explore the impact of specific CRT strategies on different language competencies beyond speaking.